Accelerated Thermal Aging Effects on Carbon‐Based Perovskite Solar Cells: A Joint Experimental and Theoretical Analysis. Issue 4 (1st March 2021) - Pica, Giovanni; Degani, Matteo; Schileo, Giorgio; Girella, Alessandro; Milanese, Chiara; Martineau, David; Andreani, Lucio C.; Grancini, Giulia
Abstract : In the search for stable perovskite photovoltaic technology, carbon‐based perovskite solar cells (C‐PSCs) represent a valid, stable solution for near‐future commercialization. However, a complete understanding of the operational device stability calls for assessing the device robustness under thermal stress. Herein, the device response is monitored upon a prolonged thermal cycle aging (heating the device for 1 month up to 80 °C) on state‐of‐the‐art C‐PSCs, often neglected, mimicking outdoor conditions. Device characterization is combined with in‐house‐developed advanced modeling of the current–voltage characteristics of the C‐PSCs using an iterative fitting method based on the single‐diode equation to extrapolate series ( R S ) and shunt ( R SH ) resistances. Two temperature regimes are identified: Below 50 °C C‐PSCs are stable, and switching to 80 °C a slow device degradation takes place. This is associated with a net decrease of the device R SH, whereas the R S is unaltered, pointing to interface deterioration. Indeed, structural and optical analyses, by means of X‐ray diffraction and photoluminescence studies, reveal no degradation of the perovskite bulk, providing clear evidence that perovskite/contact interfaces are the bottlenecks for thermal‐induced degradation in C‐PSCs. Abstract : Herein the effect of thermal aging on carbon‐based perovskite solar cells (C‐PSCs) is revealed by imposing a prolonged (27 days) temperature cycling stress. By combining device characterization and fitting modeling of the current–voltage characteristics of the C‐PSCs, a critical understanding revealing the robustness of the devices under thermal aging (up to 80 °C) and the device parameters affected is provided.